Vacuum Distillation of Aceh Patchouli Oil into Hi-Grade and Crystal Patchouli with Rotary Vacuum Evaporator - Syaifullah Muhammad; Hisbullah Hisbullah; Julia Rahmi; Fatwa Namora Ritonga; Vicky Prajaputra (Journal of Patchouli and Essential Oil Products, 2022)
Patchouli or Pogostemon cablin benth is one of the most important essential oil-producing plants in Indonesia. In the world of trade, patchouli oil is widely used as raw material, a mixing agent, and a fixative. Patchouli oil can be upgraded to Hi-Grade Patchouli (HGP) with a Patchouli alcohol (PA) content of 40-80% through vacuum distillation technology. Furthermore, HGP can be further processed into crystal patchouli with a purity of up to 90-100%. This study aims to improve the quality of patchouli oil produced by the community. This study examines the effect of variations in vacuum pressure on the distillation process on the quality of the resulting patchouli oil, determines the impact of cooling temperature variations on the resulting crystal mass, and determines the crystal quality (patchouli alcohol content and crystal size). The method used was vacuum redistillation followed by crystallization of patchouli oil. In the redistillation stage, it is carried out using a rotary vacuum evaporator. Redistillation is conducted in two stages: the first is to produce a light fraction at a temperature of 125 ℃, and the second is to produce a heavy fraction at a temperature of 140 ℃. The variable that was varied was process pressure. The pressure used is 1; 2-3; 6-8 and 10-12 mbar. The process is continued with crystallization using the cooling method (cooling crystallization) with a cooling temperature variation of -12 ℃ and -15 ℃. The results showed that through the vacuum redistillation method, the quality of patchouli oil produced by the community could be increased in PA levels up to 81.79%. The lower the operating pressure, the highest the quality of patchouli oil is produced. The lower the crystallization cooling temperature, the more crystal mass is formed. The crystal purity of this HGP resulted in very high levels of crystalline PA, namely 99.6%. The crystal size obtained is 290-600 μm on average.